Efficient representation, measurement, and recovery of spatial and social networks - Mahindre, Gunjan S., author; Jayasumana, Anura, advisor; Paffenroth, Randy, committee member; Maciejewski, Anthony, committee member; Kirby, Michael, committee member (Colorado State University. Libraries, 2021)
To view the abstract, please see the full text of the document.
Keywords: graph dimensions; missing distances; social networks; matrix completion; autoencoders; pretraining